China's Local Government Bond Market - Lam, W. Raphael (IMF Working Papers; Working Paper, 2018)
Local governments play a significant role in China's public finance and fiscal operations. The size of local government debt has grown rapidly over the past years, exceeding the stock of sovereign debt in China. How does this development compare to other countries and what policies can foster the sound development of the bond markets? This paper finds that despite its rapid growth, the local government bond market is still underdeveloped. Severe impediments-low liquidity, weak credit discipline, structural fiscal deficit in local governments-have become more visible. Reforms to develop a sound local government bond market should harmonize tax and regulations, build liquidity, and advance fiscal reforms to tighten off-budget borrowing and address intergovernmental imbalances.